Understanding the risk and protective factors associated with depressive symptoms in international students: A systematic review and meta-analysis - Tan, Shawn Raphael; Lin, Ashleigh; Fisher, Colleen; Bouras, Hamza; D'Mello, Craig; Hill, James; Hansen, Aims; Marriott, Ross (Journal of International Students, 2025)
International students face unique challenges, placing them at high risk of experiencing mental disorders. A systematic review and meta-analysis were conducted to investigate 20 predetermined, modifiable exposures associated with depressive symptoms. The literature search included cross-sectional, case‒control, and cohort studies in English. Eighty-four studies with 148,510 international tertiary students were included, 43 of which (12,721 participants) were meta-analyzed. Four exposures were significantly associated with depressive symptoms in international tertiary students: acculturative stress was most strongly associated (summary Pearson’s correlation, r = 0.44, 95% CI = 0.39 to 0.49), followed by social support (r = -0.29, 95% CI = -0.35 to -0.22), social connectedness (r = -0.26, 95% CI -0.36 to -0.15), and language (r = -0.18, 95% CI = -0.23 to -0.11). To our knowledge, this systematic review and meta-analysis are the first to quantify associations between modifiable exposures and depressive symptoms, specifically in international tertiary students.